Análise Mensal [abril de 2012] - Pereima, João Basilio; Gomes, Antônio Luiz Costa; Nascimento, Ricardo; Conceição, Ronald (Revista Economia & Tecnologia, 2012)
Juros: a suave descida A dança das moedas